Topically applied ceramide accumulates in skin glyphs - Zhang Q; Flach CR; Mendelsohn R; Mao G; Pappas A; Mack MC; Walters RM; Southall MD (Dove Medical Press, 2015)
Qihong Zhang,1 Carol R Flach,1 Richard Mendelsohn,1 Guangru Mao,2 Apostolos Pappas,2 M Catherine Mack,2 Russel M Walters,2 Michael D Southall2 1Department of Chemistry, Rutgers University, Newark, 2Johnson & Johnson Consumer Companies, Inc., Skillman, NJ, USAAbstract: Ceramides (CERs), structural components of the stratum corneum (SC), impart essential barrier properties to this thin outer layer of the epidermis. Variations in CER species within this layer have been linked to several skin diseases. A recent proliferation of CER-containing topical skin-care products warrants the elucidation of CER penetration profiles in both healthy and diseased skin. In the current study, the spatial distributions of CER concentration profiles, following topical application of two species of CER, were tracked using infrared imaging. Suspensions of single-chain perdeuterated sphingosine and phytosphingosine CER in oleic acid were applied, in separate experiments, to the surface of healthy intact ex vivo human skin using Franz diffusion cells. Following either a 24- or 48-hour incubation period at 34°C, infrared images were acquired from microtomed skin sections. Both CER species accumulated in glyph regions of the skin and penetrated into the SC, to a limited extent, only in these regions. The concentration profiles observed herein were independent of the CER species and incubation time utilized in the study. As a result, a very heterogeneous, sparse, spatial distribution of CERs in the SC was revealed. In contrast, oleic acid was found to be fairly homogeneously distributed throughout the SC and viable epidermis, albeit at lower concentrations in the latter. A more uniform, lateral distribution of CERs in the SC would likely be important for barrier efficacy or enhancement.Keywords: stratum corneum, infrared imaging, topical delivery, oleic acid